Bernstein center of supercuspidal blocks - Mishra, Manish (Journal für die reine und angewandte Mathematik, 2019)
Let 𝐆 be a tamely ramified connected reductive group defined over a non-archimedean local field k. We show that the Bernstein center of a tame supercuspidal block of 𝐆(k) is isomorphic to the Bernstein center of a depth-zero supercuspidal block of 𝐆0(k) for some twisted Levi subgroup of 𝐆0 of 𝐆.
Online erschienen: 11.08.2016
Gesehen am 27.03.2019